UPAYA LEMBAGA PENDIDIKAN ISLAM DALAM MENINGKATKAN KINERJA GURU ERA DIGITALISASI - Khoirunnisa,; Tamyis,; Endang Ekowati, (UNISAN JURNAL, 2024)
In the era of rapidly developing digitalization, the role of Islamic education management in improving teacher performance in Islamic education institutions is becoming increasingly important. This research aims to explore the impact of digitalization on Islamic education management and teacher performance in Islamic education institutions. A literature review was conducted to understand previous theories and research related to Islamic education management, teacher performance, and the implementation of technology in Islamic education. The research method used is case studies in several Islamic educational institutions that have implemented technology in their education management. Data was collected through interviews with educational institution managers and teachers, direct observation, and document analysis. The research results show that digitalization has a significant impact on Islamic education management, enabling increased efficiency in various managerial aspects such as administration, communication and curriculum management. In addition, digitalization also has the potential to improve teacher performance by providing wider access to relevant educational and training resources and facilitating collaboration and continuous learning. This research provides important insights for practitioners and policy makers in understanding how the application of technology can improve Islamic education management and teacher performance in the era of ever-growing digitalization. The conclusions and recommendations from this research provide a basis for further development efforts in utilizing the potential of technology to improve Islamic education in the future.